Identification of subsurface cavities in urban environment - Boualem BOUYAHIAOUI; Abdeslam ABTOUT; Yasser BAYOU; Mohamed BENDALI; Hassina BOUKERBOUT (Scientific Reports)
Abstract Gravimetry is the most suitable geophysical method for identifying subsurface cavities in urban or industrial environments, as it is unaffected by nearby electromagnetic disturbances. In this study, we used gravimetric geophysical method to understand the land subsidence, collapses, and fissures observed around the sealed Albian drilling site located in the M’Rara region of Northeast of Algeria. Particularly, we would like study the geological observed phenomena and its potential association with the presence of a cavity within the salt layer. According to the stratigraphic column, a salt layer was located at 936 m depth. To better understand the subsurface conditions, A new gravimetric survey was conducted to image the density distribution and identify anomalous zones associated with subsurface cavities. Various gravity data processing techniques, including polynomial fitting of different orders, vertical and horizontal gradient analysis, and three-dimensional inversion, were applied. These methods aim to evaluate the relationship between detected gravity anomalies and the underlying structures, with a focus on their possible correlation with cavities within the salt layer. The gravimetric evidence suggest that the hydraulic drilling is not the cause of the observed phenomena. These cavities are likely formed by water circulation in the subsoil, originating from the Retem Valley.